(untitled) (Research, Society and Development, 2026)
Brief psychotherapies are powerful psychological techniques for promoting collective mental health, offering psychological solutions for a wide range of problems and also present in the framework of social and health public policies. The objective of this study is to investigate, analyze, and reflect on the multidisciplinary and expanded role of current Brief Psychotherapies in promoting collective mental health. The methodology of this work is configured as an exploratory, descriptive, and narrative review of the scientific literature. The research was conducted online using three databases: PEPSIC, SCIELO, and CAPES Journals. Fifteen final studies were considered for investigation, analysis, and reflection. The results point to a multiplicity of brief, psychodynamic interventions and strategic psychotherapeutic actions in various collective and institutional contexts. This leads to a discussion of the need to strengthen primary care within the framework of social and health public policies of the Brazilian Unified Health System (SUS), as well as in addressing mental health problems lacking healthcare attention, such as in schools, hospitals, occupational settings, and institutions. Ultimately, there have been considerable studies that point to the effectiveness of brief psychotherapies in promoting collective mental health in different contexts where psychology excels. However, further studies should be conducted on a broader scale than the national context, in order to evaluate the effectiveness of brief psychotherapies in other Latin American countries, given the scarcity of research in this area, aiming to compare the data with other successful experiences of this psychotherapeutic modality.